Descrição Morfológica do Sistema Digestório do Tropidurus hispidus (Spix, 1825) - Pinto, Acacia Maria (Brasil, 2017)
Reptiles are very important for the maintenance of the environment, being considered models for biological studies because they are easily observed, manipulated and captured. Tropidurus hispidus is the most abundant lizard species in caatinga and dry environments, being very common in Brazil. Their food habit consists mainly of invertebrates, however, they can ingest parts of vegetables. Due to their differentiated dietary habits and the lack of information related to the morphology of these animals, a study of the morphological characterization of the digestive tract of Tropidurus hispidus was proposed. Four animals of both sexes of the species Tropidurus hispidus from the Apodi-RN region were used. It is necessary an in-depth study to collect more data of this correlation, so that one has a better understanding of the digestive system of the Tropidurus hispidus. Therefore, the aim of the present work is to describe the morphological characterization of the digestive tract of Tropidurus hispidus. The animals were anesthetized and euthanized. The digestive tract was dissected, fixed in Metacarn and included in paraffin. Cuttings of 5 μm thickness were stained with H & E, Gomori trichrome, Mallory trichrome and alcian blue. The digestive system of Tropidurus hispidus has a tongue with cartilaginous structure both in its central part and in the lateral, the esophagus epithelium is the pseudostratified type ciliated with goblet cells, the stomach has presented the muscular layer is well developed both in the initial part Finally, the small intestine is longer than the large intestine, but layers that form the large intestine have characteristics similar to those of the small intestine. The liver had melanomagrophagous cells and the pancreas had no islets of Langerhans, all of these differences may be mainly related to the eating habits of these animals
Morphological description of the Digestive System of the Tropidurus hispidus (Spix, 1825)
Keywords: Morfologia; Tropidurus hispidus; Sistema digestório; Morphology; Tropidurus hispidus; Digestive system; CIENCIAS AGRARIAS::MEDICINA VETERINARIA